2021
DOI: 10.3389/feart.2021.738066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Whole SST Anomaly in the Tropical Indian Ocean on Summer rainfall Over Central Asia

Abstract: The effects of sea surface temperature (SST) anomaly in the tropical Indian Ocean (IO) on summer rainfall over central Asia (CA) are investigated using NCEP/NCAR reanalysis circulation data, Hadley Centre SST data, and GPCC gridded precipitation data for 1971–2016. Results show that the SST anomalies over the whole tropical IO play important roles in modulating summer rainfall over southeast CA via the subtropical westerly jet. When the SSTs in the tropical IO are in positive phases, the south Asian monsoon is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…As displayed in Figures S1a and S1b in Supporting Information , the August precipitation in China is significantly and positively correlated with the tropical Indian Ocean and North Atlantic SST anomalies in July and August, which was also confirmed in previous studies (Meng et al., 2021; Zhao et al., 2020). In contrast, the SST anomalies related to the July and August sea ice indices are not significant neither in the tropical Indian Ocean and the North Atlantic (Figures S1c and S1d in Supporting Information ), indicating that the sea ice anomaly in the South Indian Ocean cannot affect August precipitation in China through the tropical Indian Ocean and North Atlantic SST.…”
Section: Observation Analysissupporting
confidence: 88%
“…As displayed in Figures S1a and S1b in Supporting Information , the August precipitation in China is significantly and positively correlated with the tropical Indian Ocean and North Atlantic SST anomalies in July and August, which was also confirmed in previous studies (Meng et al., 2021; Zhao et al., 2020). In contrast, the SST anomalies related to the July and August sea ice indices are not significant neither in the tropical Indian Ocean and the North Atlantic (Figures S1c and S1d in Supporting Information ), indicating that the sea ice anomaly in the South Indian Ocean cannot affect August precipitation in China through the tropical Indian Ocean and North Atlantic SST.…”
Section: Observation Analysissupporting
confidence: 88%
“…Previous studies have indicated that in recent decades, CAP has been dominated by interannual variation and is closely related to the first mode of Indian Ocean SST change, referred to as the IOBM (Meng et al., 2021; Y. Wei et al., 2023). However, the relationship between these two factors is unstable and exhibits significant interdecadal variations.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced summer South Asian precipitation following the El Nino–Southern Oscillation (ENSO) can stimulate an anomalous west‐central Asian high, affecting precipitation in the region (Ding & Wang, 2005). Additionally, the Indian Ocean Basin Mode (IOBM), which is well‐recognized as the primary mode of SST interannual variability in the tropical Indian Ocean, can also affect summer precipitation in CA by altering water vapor transport (Meng et al., 2021; Y. Wei et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Summer precipitation over Central Asia can be modulated by multiple atmospheric circulation systems, such as the South Asia high (Wei et al, 2017), westerly jet (Meng et al, 2021), the East Atlantic‐West Russia pattern (Ma et al, 2020), and North African subtropical high (Lu & Zhao, 2022). The anomalous circulation systems enhance anomalous water vapour transport into Central Asia or form an anomalous cyclone over Central Asia, eventually facilitating summer precipitation there (Chen et al, 2021; Lu & Zhao, 2022; Meng et al, 2021; Xie et al, 2021).…”
Section: Introductionmentioning
confidence: 99%